An Assessment of Bison Habitat in the Mills/Mink Lakes Area, Northwest Territories, Using Landsat Thematic Mapper Data - Matthews, Steven B. (ARCTIC, 1991)
Landsat 5 Thematic Mapper data were used to classify and map wood bison (Bison bison athabascae) habitat in an area of 3383.5 sq/km in the vicinity of Mills and Mink lakes, Northwest Territories. Digital image analysis techniques were used to enhance and classify satellite data acquired 31 August 1986 to determine the distribution and extent of forage habitats. Visual interpretation of cover types was carried out using a radiometric enhancement, consisting of a power contrast stretch, applied to spectral bands 5 (shortwave), 4 (near infrared), and 3 (red) and displayed as a colour composite image (red/green/blue). A DIPIX Technologies ARIES III image analysis system was used to perform an unsupervised classification of 16 spectral classes using a maximum likelihood classifier. The resultant thematic map was used during the summer of 1988, when aerial and ground surveys of the study area were carried out. Colour infrared photographs (1:20,000 scale) obtained in 1988 were also used as part of the reference data set to assist in selecting training areas for use in a supervised classification. Ground data were also collected during the summer of 1989 to increase the number of training areas and provide test sites for an accuracy assessment. In the final habitat classification, the ten physiognomic cover types were water, aspen forest, coniferous/mixed forest, sedge meadow, willow savanna, hordeum meadow, wetland complex, peat plateau/burned meadow, burned peat plateau, and burn-aspen regeneration. The Thematic Mapper data was geometrically corrected and smoothed using a post-classification filter. Results of the digital image analysis were produced as hard copy thematic maps and tabular summaries. Overall accuracy of the classification was 91% with the two important winter forage habitats - sedge meadow and willow savanna - having accuracies of 95% and 75% respectively. These forage habitats collectively represent 4.6% of the study area, or 153.3 sq/km. Digital image analysis of Landsat Thematic Mapper data proved ...